Mortal consequences of a cooperative action between Takotsubo syndrome and increased intracranial pressure - Gennaro Alfano; Deasy Ciervo; Teresa Migliore; Antonia Sorbo; Manuela Ariello; Andrea Vitale; Mikko O. Laukkanen; Salvatore Del Gaudio (ESC Heart Failure)
Abstract An elderly patient with head injury was registered to the emergency room. Because the patient arrived to the hospital unconscious, her cranial, cerebrovascular, and cardiac function was studied. The cardiac function measurements were (i) heart rate, (ii) blood pressure, (iii) oxygen saturation level, (iv) electrocardiogram (ECG), (v) coronary angiogram, (vi) chest computerized tomography (CT), and (vii) echocardiogram. The head damage was studied by cerebral CT and magnetic resonance imaging (MRI). The serum ischemia and inflammatory biomarkers were analysed. For the immediate treatment, the patient received cardiovascular system supporting medication. The cardiac diagnostic results were (i) the ECG suggested an elevation in the left ventricular systolic function, (ii) the blood test showed neutrophilia, increased creatine and increased troponin I kinase values, and (iii) the coronary angiogram and ECG analysis demonstrated a lack of a myocardial infarction but identified apical akinesia. The patient did not have previous symptoms of cardiovascular disease. The brain imaging demonstrated (iv) an acute ischemia in the left occipital area and (v) increased intracranial pressure. Brain MRI indicated (vi) aqueductal stenosis and (vii) multiple gliomatotic foci demonstrating hydrocephalus caused by gliomatosis cerebri. A chest CT indicated (viii) chronic obstructive pulmonary disease (COPD). One week later, the patient died because of cardiac arrest. The diagnosis was Takotsubo syndrome enforced by gliomatosis cerebri and COPD. To our knowledge, this is the first reported case in which the cardiac dysfunction of the patient is associated with gliomatosis cerebri‐derived hydrocephalus and increased intracranial pressure that together with COPD may have enhanced the negative clinical outcome.